2017
DOI: 10.1186/s12864-017-3850-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome and Transcriptome sequence of Finger millet (Eleusine coracana (L.) Gaertn.) provides insights into drought tolerance and nutraceutical properties

Abstract: BackgroundFinger millet (Eleusine coracana (L.) Gaertn.) is an important staple food crop widely grown in Africa and South Asia. Among the millets, finger millet has high amount of calcium, methionine, tryptophan, fiber, and sulphur containing amino acids. In addition, it has C4 photosynthetic carbon assimilation mechanism, which helps to utilize water and nitrogen efficiently under hot and arid conditions without severely affecting yield. Therefore, development and utilization of genomic resources for genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
144
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(150 citation statements)
references
References 83 publications
5
144
1
Order By: Relevance
“…Whereas in other types, AGG & AAG in tri, AAAG in tetra and CGTCA in penta type were most frequent in rest of the species. These results were in accordance with the previous reports in finger millet and other major crops as the mining for repeats in genomic region yielded 39 to 66% of AG/CT repeats [9,13]. The comparative low number of di-nucleotide SSRs was attributed to the reason that these repeats were often present in close vicinity of other repeats, especially penta nucleotides forming compound SSRs.…”
Section: Frequency and Distribution Of Tandem Repeatssupporting
confidence: 82%
See 4 more Smart Citations
“…Whereas in other types, AGG & AAG in tri, AAAG in tetra and CGTCA in penta type were most frequent in rest of the species. These results were in accordance with the previous reports in finger millet and other major crops as the mining for repeats in genomic region yielded 39 to 66% of AG/CT repeats [9,13]. The comparative low number of di-nucleotide SSRs was attributed to the reason that these repeats were often present in close vicinity of other repeats, especially penta nucleotides forming compound SSRs.…”
Section: Frequency and Distribution Of Tandem Repeatssupporting
confidence: 82%
“…The abundant presence of trinucleotide repeats when compared to other repeats has been reported in finger millet [19], but the recent genome-wide study has reported the presence of 58.5% of di-and 35.5% of tri-nucleotide repeats in finger millet genome [13]. However, di-nucleotide repeats were virtually absent in all the wild species except in few compound formats wherein they were found in close association along with other repeats (Figure 2).…”
Section: Frequency and Distribution Of Tandem Repeatsmentioning
confidence: 75%
See 3 more Smart Citations